Resection of Kommerell’s diverticulum in an infant with prenatal diagnosis of right aortic arch - Kenji Suzuki; Takashi Sasaki; Shinobu Kunugi; Yoshio Shima; Ryuji Fukazawa; Akira Shimizu; Takashi Nitta (Surgical Case Reports, 2019)
Abstract Background A right aortic arch is a congenital vascular anomaly that is present in up to 0.1% of pregnancies. The anomaly observed by fetal ultrasonography was recently reported to indicate vascular and chromosomal abnormalities that may complicate postnatal management. Case presentation We report the successful resection of a Kommerell’s diverticulum with left subclavian artery transfer to the left carotid artery in a 5-month-old Japanese boy. The patient was prenatally diagnosed as having a right aortic arch, and a vascular ring was confirmed at 4 months of age with enhanced computed tomography. The pathology of the resected aortic wall revealed severe disruption and fragmentation of elastic fibers associated with a disarray of smooth muscle cells in the tunica media, and cystic medial necrosis with mucoid extracellular matrix deposition. Conclusion These abnormal pathological findings supported the resection of Kommerell’s diverticulum at this point of time, and division of the ligamentum arteriosus alone was not recommended. Early intervention in this condition once the diagnosis is made may thus be advocated. The fetal diagnosis of a right aortic arch may provide a clue to the possibility of a vascular ring.